Calibrating inverted echo sounders equipped with pressure sensors - Meinen, Christopher S.; Watts, D. Randolph (DigitalCommons@URI, 1998)
The addition of an accurate pressure sensor to the inverted echo sounder (IES) has allowed for the development of a new method for calibrating the IES's acoustic travel-time record without the need for coincident conductivity-temperature-depth (CTD) or expendable bathythermograph profiles. Using this method, the round-trip travel-time measurement of the IES can be calibrated into various dynamic quantities with better accuracy than was possible with previous methods. For a set of four IES records from the Newfoundland Basin, the estimate of the accuracy of the geopotential height anomaly (integrated between 100 and 4000 db) calibrated from the IES measurements was reduced from 0.65 to 0.52 m2 s-2, which is a substantial reduction toward the intrinsic scatter of the geopotential height anomaly versus travel-time relationship for this region (0.42 m2 s-2). The addition of the pressure sensor to the IES results in reduced errors and eliminates the need for coincident CTD measurements. Moreover, the pressure sensor provides a complementary dataset recording the changes of the barotropic pressure field.